Medical students and the National Medical Commission bill: negativity and misinformation combine - Johnson, Liaquat R.; Sulfy, Junaida; Shajahan, Lishana; Vayalil, Manirsha P.; Mangalathumannil, Ananthan A. S.; Palli Thodi, Masoodha M. (International Journal Of Community Medicine And Public Health, 2018)
Background: The National Medical Commission bill (NMC bill) was drafted in response to concerns regarding medical education and healthcare in India. It seeks to reform medical education in India. However, a storm of protests by medical students and doctors erupted after it was tabled in parliament. This study was conducted to determine medical students’ knowledge of, and attitude towards the NMC bill. Methods: This cross-sectional study was conducted among medical students in a private medical college in south India. A tool based on each section of the NMC bill was developed to assess knowledge. Attitude was assessed using a 5-point Likert scale. Separate knowledge and attitude scores were computed. Statistical analyses were performed using EZR (version 1.36). Descriptive statistics, Chi-square test, logistic regression analyses were performed. Results: Only 74 (31.49%) had adequate knowledge of the NMC bill. The major source of information regarding the NMC Bill was social media (191; 81.28%), followed by newspapers (107; 45.53%). Those who were aware of the amendments to the bill; and who received information about the bill from newspapers were significantly more likely to have adequate knowledge. Participation in IMA protest rally was significantly associated with negative attitude; belonging to main (regular) batch was significantly associated with positive attitude towards the bill. Superior knowledge was not associated with positive attitude towards the bill. Conclusions: Medical students lack knowledge about the NMC bill, but have strong negative attitude towards it. Negative attitude is significantly associated with participation in IMA protest rally against NMC bill.